Canola oil compared with sesame and sesame‐canola oil on glycaemic control and liver function in patients with type 2 diabetes: A three‐way randomized triple‐blind cross‐over trial. Issue 5 (9th September 2020) - Raeisi‐Dehkordi, Hamidreza; Amiri, Mojgan; Zimorovat, Alireza; Moghtaderi, Fatemeh; Zarei, Sadegh; Forbes, Scott C.; Salehi‐Abargouei, Amin
Abstract: Background: This study aimed to compare the effects of sesame (SO), canola (CO), and sesame‐canola (SCO: a blend) oils on glycaemic control markers and liver function enzymes in adults with type 2 diabetes. Methods: In this randomized, triple‐blind, three‐way, cross‐over clinical trial, participants replaced their usual oil with the intervention oils for 9 weeks. Serum fasting blood sugar, fasting serum insulin (FSI), insulin resistance (HOMA2‐IR), beta‐cell function (HOMA2‐%B), insulin sensitivity (HOMA2‐%S), quantitative insulin sensitivity check index (QUICKI), as well as serum liver function enzymes were measured at baseline and end of intervention periods. Results: Ninety‐two participants completed all treatment periods. After adjusting for confounders, all treatment oils resulted in significant improvements in FSI and HOMA2‐%S ( p < 0.05). SO and SCO led to favourable changes in HOMA2‐IR and QUICKI ( p < 0.05). Following CO and SCO, there was a significant decrease in HOMA2‐%B ( p < 0.05). The sex‐stratified analysis revealed that FSI and HOMA2‐IR were decreased after SO compared to CO in males ( p = 0.024). Serum gamma‐glutamyltransferase (GGT) was significantly lower following SO compared to CO in females ( p = 0.02), however, the difference in change values was not significant ( p = 0.058). Conclusions: SO consumption appears to improve glycaemic control markers in males and serum GGT in females compared with CO in patients with type 2 diabetes (registration code: IRCT2016091312571N6).